2014
DOI: 10.1371/journal.pone.0104836
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Human Herpesvirus 6A/B IgG Correlates with Relapses and Progression in Multiple Sclerosis

Abstract: ObjectiveTo analyze the titers of the IgG and IgM antibodies against human herpesvirus 6A/B (HHV-6A/B) in multiple sclerosis (MS) patients treated with different disease modified therapies (DMTs) along two-years of follow-up.MethodsWe collected 2163 serum samples from 596 MS; for 301 MS patients a 2-years follow-up was performed. Serum samples of 337 healthy controls were also analyzed. Anti-HHV-6A/B IgG and IgM were analyzed by ELISA (Panbio).ResultsWe found that 129/187 (69.0%) MS patients with a decrease of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 30 publications
6
34
0
Order By: Relevance
“…As we do not have a validated cutoff for determining positivity the exact % seropositive individuals should be interpreted with caution. However, as seen in Table 2, the combined seropositivities for all three epitopes measured in study V are in the range of 75-100% that has previously been reported as HHV-6A/6B IgG seropositivity in the general population [9,11,[60][61][62][63]. As seen in Figure 20, the IgG responses against the two HHV-6B epitopes IE1B and 101K do not correlate, indicating that individuals generally do not seem to have antibodies specific for both IE1 and 101K at the same time.…”
Section: Cutoff For Serostatus and Seropositivity Resultsmentioning
confidence: 50%
See 2 more Smart Citations
“…As we do not have a validated cutoff for determining positivity the exact % seropositive individuals should be interpreted with caution. However, as seen in Table 2, the combined seropositivities for all three epitopes measured in study V are in the range of 75-100% that has previously been reported as HHV-6A/6B IgG seropositivity in the general population [9,11,[60][61][62][63]. As seen in Figure 20, the IgG responses against the two HHV-6B epitopes IE1B and 101K do not correlate, indicating that individuals generally do not seem to have antibodies specific for both IE1 and 101K at the same time.…”
Section: Cutoff For Serostatus and Seropositivity Resultsmentioning
confidence: 50%
“…Both studies performed by us (Study IV) and others [9,11,[60][61][62][63] have detected IgG antibodies against HHV-6A/6B in >75% of the general population. The problem with antibody assays used, at least until now, is that they have not been able to distinguish between antibodies against HHV-6A and HHV-6B.…”
Section: Antibody Studiesmentioning
confidence: 68%
See 1 more Smart Citation
“…A 2012 study of a Tasmanian cohort found HHV-6 IgG titer to be a significant predictor of relapse risk [27]. This was echoed in a 2014 study of a Spanish MS cohort, which reported that a decrease in HHV-6 antibody titers correlated with fewer relapses and less disease progression [28]. Interestingly, the authors noted that IgG titers reached their highest value two weeks, and IgM titers one month, before relapse [28].…”
Section: Traces Of Hhv-6 In the Periphery: Virus Detection And Virus-mentioning
confidence: 99%
“…This was echoed in a 2014 study of a Spanish MS cohort, which reported that a decrease in HHV-6 antibody titers correlated with fewer relapses and less disease progression [28]. Interestingly, the authors noted that IgG titers reached their highest value two weeks, and IgM titers one month, before relapse [28]. A 2011 study of a Latvian MS cohort reported HHV-6 DNA in the plasma of a majority of RRMS and SPMS patients during relapse, which was confirmed by enhancing MRI lesions, and correlated with higher serum concentrations of the inflammatory cytokines IL-12 and TNF-alpha relative to periods of remission [29].…”
Section: Traces Of Hhv-6 In the Periphery: Virus Detection And Virus-mentioning
confidence: 99%